2019
DOI: 10.1101/715136
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estrogen deprivation triggers an immunosuppressive phenotype in breast cancer cells

Abstract: Estrogen receptor (ER)-positive breast tumors are routinely treated with estrogen-depriving therapies. Despite their effectiveness, patients often progress into a more aggressive form of the disease. Through a chemical screen oriented to identify chemicals capable of inducing the expression of the immune-checkpoint ligand PD-L1, we found antiestrogens as hits. Subsequent validations confirmed that estrogen deprivation or ERa depletion induces PD-L1 expression in ER-positive breast cancer cells, both in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…These discrepancies may be attributable to the different regimens used, suggesting the need for studies with more samples and corresponding pathological assessment. In addition, ER + BC cells grown under estrogen-free conditions presented an upregulation of PD-L1 as a result of ERα signaling abrogation [81], corroborating the possibility of combining NET with immunotherapy in ER + BC.…”
Section: The Effects Of Estrogen Deprivation On the Immune Microenvirsupporting
confidence: 52%
See 2 more Smart Citations
“…These discrepancies may be attributable to the different regimens used, suggesting the need for studies with more samples and corresponding pathological assessment. In addition, ER + BC cells grown under estrogen-free conditions presented an upregulation of PD-L1 as a result of ERα signaling abrogation [81], corroborating the possibility of combining NET with immunotherapy in ER + BC.…”
Section: The Effects Of Estrogen Deprivation On the Immune Microenvirsupporting
confidence: 52%
“…In addition, Joffroy et al [12] found that tamoxifen-or fulvestrant-induced TGFβ production in MCF-7 cells led to a decreased cytotoxic effect of CD8 + T cells as well as an increased polarization of CD4 + T cells into Foxp3 + Tregs, which futher supported the development of endocrine resistance. Moreover, ERα signaling blockade or depletion by tamoxifen or fulvestrant evoked the upregulation of programmed deathligand 1 (PD-L1) in multiple ER + BC cell lines, contributing to the cytotoxic T cell evasion of BC cells [81]. The inverse correlation between ERα and PD-L1 was confirmed not only in the MMTV-PyMT transgenic mouse model [81] but also in human BC specimens, where the ratio of PD-L1 positive patients was much lower in ER+/HER2− BC (19.4%) than in triple-negative breast cancer (TNBC, 58.6%) [82,83].…”
Section: The Effects Of Serms and Serds On The Tumor Immune Microenvimentioning
confidence: 99%
See 1 more Smart Citation
“…Since estrogen presence in tumor microenvironment can also play a significant immunosuppressive role by promoting tolerance of weakly immunogenic tumor cells [69], the use of antiestrogen therapies in combination with aromatase inhibitors could be a rational strategy to enhance the response to immunotherapies. However, although adjuvant hormonal therapy combined with HER2-targeted agents in hormone receptor-positive and HER2-positive breast cancer patients already represents a standard treatment, recent studies have shown that estrogen deprivation promotes transcriptional programs that favor immune evasion and increases PD-L1 expression in metastasis arising from breast cancer patients receiving adjuvant hormonal therapy for their local disease [85]. For this reason, the use of hormone-therapies in combination with PD-1/PD-L1 blocking immunotherapies should be thoroughly investigated.…”
mentioning
confidence: 99%
“…ER-α regulates gene transcription through the direct binding of the receptor to regulatory regions (enhancers or silencers) of target genes [56]. The relationship between ER-α and PD-L1 has been cemented in a study that revealed estrogen deprivation or ER-α depletion induced PD-L1 expression in ER+ breast cancer in vitro and in vivo [66]. While acknowledging how the regulation of IC molecular expression occurs in a bidirectional manner, we propose the master regulators of ICs as the transcription factors located at a hub of a regulatory network or as the direct transcriptional regulator responsible for the gene expression of co-inhibitory (or co-stimulatory) ICs.…”
Section: Known Putative Master Regulators Of Icsmentioning
confidence: 99%